2021
DOI: 10.1525/elementa.2020.20.00161
|View full text |Cite
|
Sign up to set email alerts
|

Orphaned oil and gas well stimulus—Maximizing economic and environmental benefits

Abstract: Orphaned oil and gas wells are abandoned wells for which the cost of environmental impacts usually falls on governments and the general public. Government agencies responsible for well plugging often face funding shortfalls and many orphaned wells remain unplugged. To address this and support the oil and natural gas industry, federal governments are already spending, or considering spending, billions of dollars to plug orphaned oil and gas wells. Here, we analyze oil and gas data for the United States and Cana… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
25
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
2
1

Relationship

2
4

Authors

Journals

citations
Cited by 15 publications
(26 citation statements)
references
References 59 publications
(78 reference statements)
0
25
1
Order By: Relevance
“…Understanding the role of well attributes and other factors, such as oil/gas prices, on the number of newly orphaned wells may provide insight into why and when wells are becoming orphaned. For example, a study found a large spike in orphan well numbers in Alberta when oil prices dropped in 2016 to 2018 . To our knowledge, state oil and gas agencies or other data sources do not track the number of documented orphaned wells over time.…”
Section: Introductionmentioning
confidence: 95%
See 2 more Smart Citations
“…Understanding the role of well attributes and other factors, such as oil/gas prices, on the number of newly orphaned wells may provide insight into why and when wells are becoming orphaned. For example, a study found a large spike in orphan well numbers in Alberta when oil prices dropped in 2016 to 2018 . To our knowledge, state oil and gas agencies or other data sources do not track the number of documented orphaned wells over time.…”
Section: Introductionmentioning
confidence: 95%
“…Orphaned oil and gas wells are a category of unplugged nonproducing wells for which the operator is unknown, unavailable, or insolvent, leaving no responsible party to plug the well and restore the well site other than government agencies and the general public. Orphaned wells can pose a wide range of environmental risks by acting as leakage pathways connecting oil and gas reservoirs to groundwater aquifers and the atmosphere. As such, they can be a potential source of groundwater contamination, air pollution, ecosystem degradation, human health impacts, and greenhouse gas emissions, in particular, methane, a potent greenhouse gas. …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, groundwater samples are typically collected within 200 m of the surface [29], which is shallow relative to depths of most oil and gas activities, which generally occur at depths greater than 1000 m [30] (figure S1 available online at stacks.iop.org/ERL/17/014014/mmedia). Based on available studies detailing oil and gas well leakage and the abundance of oil and gas wells in Canada and the United States (US) [31], oil and gas wells may potentially act as a pathway through which surface P enters the subsurface. To obtain indications of the broad potential effects of oil and gas wells on P concentrations in groundwater as a source and/or leakage pathway (SM: Oil and gas: contamination sources and leakage pathways), we analyze oil and gas well distributions and available concentrations of P in groundwater.…”
Section: Introductionmentioning
confidence: 99%
“…In the 21st century, the proliferation of shale gas and tight oil development, which typically involves deep, horizontally drilled wells, has raised concerns that decommissioning costs for these wells may exceed those of conventional wells because of the former’s greater depths and associated pressure, e.g., ref . In 2020, as oil prices crashed due to a global oversupply initiated by the effects of the COVID-19 pandemic, considerable interest emerged among state and federal policymakers to decommission wells as a way to support unemployed oil and gas workers and to reduce the environmental and climate risks of unplugged abandoned wells, e.g., refs .…”
Section: Introductionmentioning
confidence: 99%